m-4m+12=3

Simple and best practice solution for m-4m+12=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-4m+12=3 equation:


Simplifying
m + -4m + 12 = 3

Reorder the terms:
12 + m + -4m = 3

Combine like terms: m + -4m = -3m
12 + -3m = 3

Solving
12 + -3m = 3

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -3m = 3 + -12

Combine like terms: 12 + -12 = 0
0 + -3m = 3 + -12
-3m = 3 + -12

Combine like terms: 3 + -12 = -9
-3m = -9

Divide each side by '-3'.
m = 3

Simplifying
m = 3

See similar equations:

| 5x+10=9x+15 | | [(x-2)-5][(x-2)+3]=0 | | 18+2x=-54 | | 17x+64=13 | | -256=8(7X-6)-4X | | 24x+7*8= | | 5a-2+b-3b+2a= | | 5x-3x+40=50 | | x+109=1+89 | | 3x^2-8x-19=0 | | 70=-17.5n | | 2x=3x-10 | | 12v-3(2+4v)+6= | | 6(1-6X)-4(3X+6)=30 | | -15x+7x+1=3-8 | | 3x^2-22x=0 | | 3x^2-32x-19=0 | | 20x^3-8x^2-5x+2=0 | | 100-x=-39 | | 40-x=-5 | | -4(y-3)+6=2(2y-2)+5y+5 | | 6n^3-24n^2+n-4=0 | | 5+n-p+2n-4= | | 4x-3y=42 | | 4x+3y=42 | | [2x+4]=8 | | 1+1+1=A | | 2(2t+5-2t)+8t= | | 6456*6557-7567+6678/66788+(676+9*5)=s | | m^2+2m-12=0 | | -(y-11)=-3 | | 8a+11=3a-41 |

Equations solver categories